VARIETAS TANAMAN, KOMPOS, DAN CARA PENGAIRAN SEBAGAI KOMPONEN PENGENDALI PENYAKIT HAWAR UPIH PADI - , BAMBANG NURYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Rice sheath blight caused by Rhizoctonia solani Kühn has been widely distributed at rice growing areas in Central Java and Yogyakarta provinces. The disease develops well in lowland rice field (0â200 m above sea level) and develops more severe on semidwarf high yielding rice varieties. Increasing degree of disease severity is correlated not only with increasing temperature and relative humidity under plant canopy but also with decreasing conductivity and soil pH. Sclerotia and mycelia of R. solani were widely spreaded in the rice field might play a major role as primary inocula of sheath blight disease, should be considered to control the disease which oriented to the density and potency of initial inoculum. In the same niche, R. solani interacted with other soil microorganisms, resulted in depressing growth or even death of R. solani. Isolated antagonistic bacteria from soil surface containing organic matter were able to suppress vegetative growth of R. solani as high as 46.5% in potato agar medium and suppressed sheath blight lesion as high as 80.3% in vitro test. Management of organic matter particularly mature compost could suppress the disease. Mature compost suppressed sclerotial germinations of R. solani for about 14.0% and improving mature compost with bacterial antagonistic suppressed sclerotial germinations about 28.0%. In contrast, amending substrate by fresh organic matter triggered R. solani to grow. Tall type and low-tillering rice plant like Cimelati variety showed reducing effect on disease severity of sheath blight. Cimelati phenotype caused environmental conditions under plant canopy as temperature and relative humidity were lower than condition on Ciherang and hybrid rice of Maro. This microclimate was not favorable for sheath blight development. Relative humidity under plant canopy decreased about 2.8% and 4.4%, in bed flooding irrigation arounded canal and bed irrigation once a week, respectively. Integration of Cimelati rice variety and uncontinuous flooding irrigation was effective for decreasing disease severity of rice sheath blight. Sheath blight control by integration of some epidemic components has a high chance of success to suppress the disease severity.